2014
DOI: 10.1021/nl501942w
|View full text |Cite
|
Sign up to set email alerts
|

Gated Hall Effect of Nanoplate Devices Reveals Surface-State-Induced Surface Inversion in Iron Pyrite Semiconductor

Abstract: Understanding semiconductor surface states is critical for their applications, but fully characterizing surface electrical properties is challenging. Such a challenge is especially crippling for semiconducting iron pyrite (FeS2), whose potential for solar energy conversion has been suggested to be held back by rich surface states. Here, by taking advantage of the high surface-to-bulk ratio in nanostructures and effective electrolyte gating, we develop a general method to fully characterize both the surface inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 49 publications
4
48
0
Order By: Relevance
“…These states may result from bulk/intrinsic sulfur vacancies that generate interrupted charge distribution and a very narrow surface space charge region thus limiting the total barrier height. Hence the literature suggests that the photovoltage/photocurrent and photoconversion efficiency of iron pyrite thin film solar cells can be improved by controlling and passivating bulk defects and intrinsic surface states …”
Section: Doped Pyrite For Photovoltaicsmentioning
confidence: 98%
“…These states may result from bulk/intrinsic sulfur vacancies that generate interrupted charge distribution and a very narrow surface space charge region thus limiting the total barrier height. Hence the literature suggests that the photovoltage/photocurrent and photoconversion efficiency of iron pyrite thin film solar cells can be improved by controlling and passivating bulk defects and intrinsic surface states …”
Section: Doped Pyrite For Photovoltaicsmentioning
confidence: 98%
“…Some recent studies on pyrite single crystals revealed the existence of as urface inversion layera nd band bendinga tt he surface. [9,21,64] Although no consensush as been reached on the origin of the inversion layer, researchers broadly agree that it is caused by ac omplex electronic structure of the surface layer. Thus,i tw ould be beneficial to investigate the surface and bulk conduction characteristics to shed some light on this issue.T here is no direct experimental method to study the differential surface and bulk conduction.…”
Section: Iron Pyrite Single-crystald Evicementioning
confidence: 99%
“…Despite the fact that a lot of attempts such as morphology control or ligand protection have been tried,[11b‐d] the device efficiency has not improved significantly in the past 20 years . Several possible explanations have been suggested for the low V OC , including bulk non‐stoichiometry, near‐surface non‐stoichiometry (resulting in a metallic FeS‐like surface layer), sulfur vacancies that generate electronic states in the band gap, Fermi level pinning induced by surface states, or small band gap phases (pyrrhotite, troilite, and marcasite) present as domains in bulk pyrite . Orthorhombic marcasite (FeS 2 ) and hexagonal troilite (FeS) are believed to be detrimental phases for photochemical performance, as they have much smaller band gaps (0.04 eV for troilite and 0.34 eV for marcasite), and it has been suggested that even trace amounts of these phases would cause the low V OC reported for pyrite films .…”
mentioning
confidence: 99%